Competency Mapping of Vocational Education Graduates of South Sumatra Province Based on Leading Industries Using Input-Output Analysis - Lupikawaty, Marieska; Novianti, Leni; Handayani, Ade Silvia; Rakhman, M.Arief (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The alignment between educational and industrial needs is an important factor in driving economic growth and workforce readiness. In South Sumatra Province, vocational high schools and polytechnics play a crucial role in equipping students with the technical and practical skills necessary for employment in key sectors such as plantations, feed, oil and gas, and coal-based industries. However, there is a gap between the competencies offered by educational institutions and the demands of the growing industry, especially in emerging areas such as digital transformation and sustainability. This study aims to map the competence of vocational schools and polytechnics to leading industries in South Sumatra using Geographic Information Systems (GIS) and input-output analysis. GIS is used to analyze the spatial distribution of educational institutions and their proximity to industrial centers, while input-output analysis assesses competency flows into industry-specific needs. Data on educational programs, graduate output, and industry requirements are compiled and analyzed to identify gaps and areas for improvement. The results reveal strong alignment in traditional industries such as rubber, palm oil, and mining, while significant gaps are observed in emerging areas such as green energy and digital technologies. Urban areas such as Palembang were found to have a higher concentration of educational institutions and diverse programs, while rural areas faced limited access to specialized training. The study emphasizes the importance of modernizing curriculum, investing in infrastructure, and encouraging industry-education collaboration to address these gaps.